Effects of mine tailing exposure on early life stages of cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) - Farkas, Julia; Nordtug, Trond; Svendheim, Linn Hjelmeland; Amico, Elettra D.; Davies, Emlyn John; Ciesielski, Tomasz Maciej; Jenssen, Bjørn Munro; Kristensen, Torstein; Olsvik, Pål Asgeir; Hansen, Bjørn Henrik (Environmental Research, 2021)
publishedVersion